The optimal pulse pressures for healthy adults with different ages and sexes correlate with cardiovascular health metrics - Chou, Chung-Hsing; Yin, Jiu-Haw; Lin, Yu-Kai; Yang, Fu-Chi; Chu, Ta-Wei; Chuang, Yuan Chieh; Lin, Chia Wen; Peng, Giia-Sheun; Sung, Yueh-Feng (Frontiers in Cardiovascular Medicine, 2022)
Background Pulse pressure (PP) may play a role in the development of cardiovascular disease, and the optimal PP for different ages and sexes is unknown. In a prospective cohort, we studied subjects with favorable cardiovascular health (CVH), proposed the mean PP as the optimal PP values, and demonstrated its relationship with healthy lifestyles. Methods and results Between 1996 and 2016, a total of 162,636 participants (aged 20 years or above; mean age 34.9 years; 26.4% male subjects; meeting criteria for favorable health) were recruited for a medical examination program. PP in male subjects was 45.6 ± 9.4 mmHg and increased after the age of 50 years. PP in female subjects was 41.8 ± 9.5 mmHg and increased after the age of 40 years, exceeding that of male subjects after the age of 50 years. Except for female subjects with a PP of 40–70 mmHg, PP increase correlates with both systolic blood pressure (BP) increase and diastolic BP decrease. Individuals with mean PP values are more likely to meet health metrics, including body mass index (BMI) <25 kg/m2 (chi-squared = 9.35, p<0.01 in male subjects; chi-squared = 208.79, p < 0.001 in female subjects) and BP <120/80 mmHg (chi-squared =1,300, p < 0.001 in male subjects; chi-squared =11,000, p < 0.001 in female subjects). We propose a health score (Hscore) based on the sum of five metrics (BP, BMI, being physically active, non-smoking, and healthy diet), which significantly correlates with the optimal PP. Conclusion The mean PP (within ±1 standard deviation) could be proposed as the optimal PP in the adult population with favorable CVH. The relationship between health metrics and the optimal PP based on age and sex was further demonstrated to validate the Hscore.